Ultraviolet protection of recycled polyethylene terephthalate. Issue 32 (29th April 2017) - Curtzwiler, Greg W.; Williams, Eric B.; Maples, Austin L.; Davis, Nathan W.; Bahns, Ted L.; Eliseo De León, J.; Vorst, Keith L.
ABSTRACT: Polyethylene terephthalate (PET) is commonly used for food packaging due to its high clarity, high resistance to water vapor, oxygen and carbon dioxide permeation, and good mechanical properties. However, its high transmittance in the ultraviolet‐A (UVA) region leaves food susceptible to UV‐induced degradation reactions. Incorporating post‐consumer recycled (PCR) PET into virgin PET increased UVA absorption 100% when utilizing 100% PCR‐PET, thus, increasing the protection potential of food packaging by reducing UVA‐induced degradation reactions. Comparison of the current data with previous work demonstrated the reproducibility of UVA protection independent of the PC flake source. The thickness‐normalized absorbance at 350 nm was a reliable predictor of the UVA protection potential regardless of composition and manufacture date. Raman, fluorescence, and attenuated total reflectance‐Fourier transform infrared spectroscopy analyses provided support that the UVA absorbing moiety was a quinone derivative formed during degradation reactions that are known to occur during melt processing/re‐processing. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45181. Abstract :